BCI Software Platforms. - Brunner, Clemens; Andreoni, G; Bianchi, L; Benjamin Blankertz; Breitwieser, C.; Kanoh, S.; Kothe, C. A.; Lecuyer, A.; Makeig, S; Mellinger, J.; Perego, P.; Renard, Y.; et al. (Towards Practical Brain-Computer Interfaces, 2013)
In this chapter, we provide an overview of publicly available software platforms for brain–computer interfaces. We have identified seven major BCI platforms and one platform specifically targeted towards feedback and stimulus presentation. We describe the intended target user group (which includes researchers, programmers, and end users), the most important features of each platform such as availability on different operating systems, licences, programming languages involved, supported devices, and so on. These seven platforms are: (1) BCI2000, (2) OpenViBE, (3) TOBI Common Implementation Platform (CIP), (4) BCILAB, (5) BCI++, (6) xBCI, and (7) BF++. The feedback framework is called Pyff. Our conclusion discusses possible synergies and future developments, such as combining different components of different platforms. With this overview, we hope to identify the strengths and weaknesses of each available platform, which should help anyone in the BCI research field in their decision which platform to use for their specific purposes.

Current Trends in Hardware and Software for Brain-Computer Interfaces (BCIs). - Peter Brunner; Bianchi, L; Guger, C; Cincotti, F; Gerwin Schalk (J Neural Eng, 2011)
A brain-computer interface (BCI) provides a non-muscular communication channel to people with and without disabilities. BCI devices consist of hardware and software. BCI hardware records signals from the brain, either invasively or non-invasively, using a series of device components. BCI software then translates these signals into device output commands and provides feedback. One may categorize different types of BCI applications into the following four categories: basic research, clinical/translational research, consumer products, and emerging applications. These four categories use BCI hardware and software, but have different sets of requirements. For example, while basic research needs to explore a wide range of system configurations, and thus requires a wide range of hardware and software capabilities, applications in the other three categories may be designed for relatively narrow purposes and thus may only need a very limited subset of capabilities. This paper summarizes technical aspects for each of these four categories of BCI applications. The results indicate that BCI technology is in transition from isolated demonstrations to systematic research and commercial development. This process requires several multidisciplinary efforts, including the development of better integrated and more robust BCI hardware and software, the definition of standardized interfaces, and the developmentof certification, dissemination and reimbursement procedures.
Keywords: Biofeedback, Psychology; Brain; Brain Mapping; Electroencephalography; Equipment Design; Equipment Failure Analysis; Humans; Man-Machine Systems; Software; User-Computer Interface

BCI meeting 2005 - Workshop on Technology: Hardware and Software. - Cincotti, F; Bianchi, L; Birch, Gary; Guger, C; Mellinger, Jürgen; Scherer, Reinhold; Schmidt, Robert N; Yáñez Suárez, Oscar; Gerwin Schalk (IEEE Trans Neural Syst Rehabil Eng, 2006)
This paper describes the outcome of discussions held during the Third International BCI Meeting at a workshop to review and evaluate the current state of BCI-related hardware and software. Technical requirements and current technologies, standardization procedures and future trends are covered. The main conclusion was recognition of the need to focus technical requirements on the users' needs and the need for consistent standards in BCI research.
Keywords: Algorithms; Biotechnology; Brain; Communication Aids for Disabled; Computers; Electroencephalography; Equipment Design; Humans; Internationality; Man-Machine Systems; Neuromuscular Diseases; Software; User-Computer Interface